2000
DOI: 10.1098/rspb.2000.1229
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of word length and visual contrast in the fusiform and lingual gyri during

Abstract: Previous studies have shown differential responses in the fusiform and lingual gyri during reading and suggested that the former is engaged in processing local features of visual stimuli and the latter is engaged in global shape processing. We used positron emission tomography in order to investigate how these regions are modulated by two common variables in reading: word length (three, six and nine letters) and perceptive similarity to the background (high and low contrast). Increasing both word length and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
146
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(171 citation statements)
references
References 21 publications
22
146
3
Order By: Relevance
“…Significance was not, however, reached for the subgroup of earliest cType I sources which were selected for the ROI analysis. A length effect around the occipital midline is in agreement with hemodynamic data of Mechelli et al (2000) and Indefrey et al (1997). It is noteworthy that not even the criterion search suggested length effects in activation patterns reminiscent of the Type II response.…”
Section: Effects Of Letter-string Lengthsupporting
confidence: 77%
“…Significance was not, however, reached for the subgroup of earliest cType I sources which were selected for the ROI analysis. A length effect around the occipital midline is in agreement with hemodynamic data of Mechelli et al (2000) and Indefrey et al (1997). It is noteworthy that not even the criterion search suggested length effects in activation patterns reminiscent of the Type II response.…”
Section: Effects Of Letter-string Lengthsupporting
confidence: 77%
“…33 Moreover, cerebellar gray matter volume has previously been linked to nonverbal IQ, 34 and occipital cortex and lingual gyrus are associated with mathematical and advanced reading skills. 35,36 Interestingly, similar to results in patients after their exposure in the present study, children with 22q11.2 deletion syndrome also experience reductions in gray matter density in the anterior cerebellum that are associated with deficits in performance IQ and language delay. 37 However, it is important to note that because we used a conservative approach to detect group differences, the identified regions were relatively small and the exploratory analysis would not survive correction for the tens of thousands of voxels across the entire brain volume, thereby increasing the risk of a type I error.…”
Section: Figuresupporting
confidence: 73%
“…Two recent studies of reading, one using PET (Mechelli, Humphreys, Mayall, Olson, & Price, 2000) and one using fMRI (Indefrey et al, 1997), revealed monotonic increases in signal strength as a function of word length. These effects were visible in the midline posterior occipital cortex, bordering on the fusiform gyrus.…”
Section: Letter String Lengthmentioning
confidence: 99%